(untitled) (Journal of Management and Social Sciences, 2025)
Abstract: The integrity of financial reports is fundamental to economic stability and investor confidence. This paper investigates the significant roles of accounting ethics and governance integrity in restoring public confidence in financial reporting in Nigeria. A quantitative research approach was employed, utilizing a questionnaire for data collection. Descriptive analysis was used to interpret the data. The research found that the majority of respondents believe that accounting ethics and governance integrity can restore public confidence in financial reporting in Nigeria. The study also identified significant roles and challenges facing the implementation of accounting ethics, including pressures to manipulate financial data, and obstacles to applying governance mechanisms to restore public trust in financial reporting in Nigeria. The paper concludes by advocating for the adoption of accounting ethics and governance integrity as indispensable tools for rebuilding confidence in the financial reporting landscape in Nigeria. It recommends prioritizing the protection of whistleblowers and underscores the importance of fostering a culture of integrity, transparency, and accountability to promote investor confidence, good governance, and economic growth in Nigeria. Keywords: Accounting ethics, governance integrity, restoring public confidence, financial reporting landscape, Nigeria.